Optical Flow Active Contours with Primitive Shape Priors for Echocardiography. (24th September 2009) - Hamou Hamou, Ali K. Ali K.; El-Sakka El-Sakka, Mahmoud R. Mahmoud R.
Abstract : Accurate delineation of object borders is highly desirable in echocardiography, especially at the left ventricle. Among other model-based techniques, active contours (or snakes) provide a unique and powerful approach to image analysis. In this work, we propose the use of a new external energy for a gradient vector flow (GVF) snake, being the optical flow of a moving sequence (modeling the mechanical movement of the heart). This external energy can provide additional information to the active contour model garnering adequate results for moving sequences. An automatic iterative primitive shape prior was also applied in order to further improve the results of a GVF snake, when dealing with especially noisy echocardiographic images. Results were compared with expert-defined segmentations yielding acceptable sensitivity, precision rate and overlap ratio performance.